EMKONTAN learning model to improve creativity, collaborative skills, and environmental literacy of prospective biology teachers - Nurwidodo, N.; Hindun, Iin (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2024)
EMKONTAN is a student-centered learning model, which is oriented in creative learning, problem-solving (problem-based learning), collaborative learning, and giving opportunity for students to improve their environmental literacy. This study aims to analyze the validity and practicality of the EMKONTAN model in improving creativity, collaborative skills, and environmental literacy of prospective biology teachers. This study was carried out in the even semester of the academic year of 2020/2021 at IKIP Budi Utomo Malang and Faculty of Teacher Training and Education, Universitas Muhammadiyah Malang. This study involved 150 students in an even semester (Semester II) thru total sampling. Validity instruments used in this study comprised validation sheets for material, method, and media experts. Meanwhile, the instruments for practicality used observation sheets which were focused on the learning implementation, relevant student activities, and obstacles found during the learning processes. The results of the EMKONTAN model indicate that the model has content validity, constructs, and faces that are very feasible to be implemented in the learning process. Additionally, the results of practicality for the EMKONTAN model involve the implementation for each syntax with an average score of <3,6 in a very good category; the students’ activities are in a very active category with the average score of <85%, and the obstacle found is pandemic period; thus, online learning is required. Yet, the risks can decrease the effectiveness of learning. The implication of this research is that the application of the EMKOTAN model in universities by lecturers in related subjects will support efforts to increase environmental literacy for prospective biology teacher students.